2023
DOI: 10.3389/fnins.2023.1129688
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture and manual acupuncture at LR3 and ST36 have attenuating effects on hypertension and subsequent cognitive dysfunction in spontaneously hypertensive rats: A preliminary resting-state functional magnetic resonance imaging study

Abstract: IntroductionChronic hypertension may have a contributory role toward cognitive impairment. Acupuncture exerts protective effects on cognitive functions while controlling the blood pressure. However, the neural mechanism underlying the dual attenuating effect of acupuncture remains unclear. In this study, we investigated the effects of electroacupuncture (EA) and manual acupuncture (MA) on the functional activity of the brain regions of spontaneously hypertensive rats (SHRs) by through resting-state functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…With regard to the difference between the effects of EA and MA on cognitive impairment, it is generally recognized that EA stimulation shows a more beneficial effect on neurodegenerative diseases ( Lin et al, 2018 ). Studies found that EA activated more callback brain regions and functional connectivity than MA ( Liu et al, 2023 ) due to the electrical twitching of surrounding tissues it produced ( Yamamoto et al, 2011 ). However, some studies ( Mitchell and Shiri-Feshki, 2008 ) instead found that patients who received MA displayed a significant improvement in cognitive function compared to those who received EA.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the difference between the effects of EA and MA on cognitive impairment, it is generally recognized that EA stimulation shows a more beneficial effect on neurodegenerative diseases ( Lin et al, 2018 ). Studies found that EA activated more callback brain regions and functional connectivity than MA ( Liu et al, 2023 ) due to the electrical twitching of surrounding tissues it produced ( Yamamoto et al, 2011 ). However, some studies ( Mitchell and Shiri-Feshki, 2008 ) instead found that patients who received MA displayed a significant improvement in cognitive function compared to those who received EA.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be associated with the activation of brain regions, including the paraventricular nucleus of the hypothalamus, arcuate nucleus, periaqueductal gray matter in the ventrolateral funiculus, and rostral ventrolateral medulla after acupuncture. [20–22] These activations reduce the excitability of the sympathetic nervous system and enhance vagal activity. The research has demonstrated that acupuncture at Fengchi (GB 20) can increase the expression of neuronal nitric oxide synthase in the arcuate nucleus and periaqueductal gray matter surrounding the ventrolateral aqueduct, inhibiting the activity of the sympathetic nervous system, thereby reducing blood pressure.…”
Section: Discussionmentioning
confidence: 99%